Approaching Yehud : new approaches to the study of the Persian period - Berquist, Jon L. (Semeia studies, 2007)
The long-held view that the Persian period in Israel (known as Yehud) was a historically derivative era that engendered little theological or literary innovation has been replaced in recent decades by an appreciation for the importance of the Persian period for understanding Israel's literature, religion, and sense of identity. A new image of Yehud is emerging that has shifted the focus from viewing the postexilic period as a staging ground for early Judaism or Christianity to dealing with Yehud on its own terms, as a Persian colony with a diverse population. Taken together, the thirteen chapters in this volume represent a range of studies that touch on a variety of textual and historical problems to advance the conversation about the significance of the Persian period and especially its formative influence on biblical literature. --From publisher's description.